Studies on the orthogonal effects in seismic analyses - Hisada, Toshihiko, 1914- (KICT report (Kajima Institute of Construction Technology), 1987)
"Observation of past earthquake damage to buildings shows that corner columns are apt to suffer damage ... reasons for this might be intricate responses due to orthogonal effects."--p. 1.